The Spationary : A Dictionary of Essential Space Terminology for Lawyers - Rapp, Lucien, (International Law E-books Online, Collection 2026, 2025)
This book enables readers to find, in a few moments, terms that they can use immediately or reprocess for the drafting of a legal text, a ruling, a contract or a scientific paper. For each of the 218 terms identified, a simple definition and a few additional elements are proposed. Where possible, entries also include examples, jurisprudence and doctrine. The purpose of this space dictionary is to be leafed through as needed to perfect the reader's knowledge. It will be updated regularly. The Spationary is an invaluable resource, providing answers to simple queries; a simple, rapid and highly operational introduction to the international corpus juris spatialis ; and an element of playfulness, because it is often through playful engagement with words and their definitions that a reader who may feel like an outsider can move into a universe or a scientific discipline.